Justifications for the Spanish Invasion of North Africa (16th Century) - Bilgin, Feridun (Journal of Al-Tamaddun, 2021)
The process called Reconquista (Reconquest) in history of Spain succeeded with the occupation of Granada (1492). In order to prevent its lands from becoming “Andalusia” again, the Spanish government established the country’s lines of defense outside the country in North Africa. Considering religious, commercial, political and military reasons a limited occupation policy was implemented in North Africa. Places on strategic North African coasts such as Ceuta, Melilla, Oran and Merselkebir were occupied, and military garrisons (Presedios/Plazas) were established here. With the help of these garrisons, the Spain’s Mediterranean and Atlantic trade has been secured for decades.